2016
DOI: 10.18632/oncotarget.6870
|View full text |Cite
|
Sign up to set email alerts
|

Human carcinoma-associated mesenchymal stem cells promote ovarian cancer chemotherapy resistanceviaa BMP4/HH signaling loop

Abstract: The tumor microenvironment is critical to cancer growth and therapy resistance. We previously characterized human ovarian carcinoma-associated mesenchymal stem cells (CA-MSCs). CA-MSCs are multi-potent cells that can differentiate into tumor microenvironment components including fibroblasts, myofibroblasts and adipocytes. We previously reported CA-MSCs, compared to normal MSCs, express high levels of BMP proteins and promote tumor growth by increasing numbers of cancer stem-like cells (CSCs). We demonstrate he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 54 publications
(78 reference statements)
5
99
0
1
Order By: Relevance
“…The distinct expression profile of CA‐MSCs corresponds with unique protumorigenic functions: (a) CA‐MSCs increase the CSC pool as marked by increased levels of ALDH and enhanced tumor sphere formation , and CA‐MSCs enhance (b) tumor growth and (c) chemotherapy resistance . Therefore, we determined if cancer stimulated OM MSCs classified as CA‐MSCs also developed CA‐MSC‐associated protumorigenic functions.…”
Section: Resultsmentioning
confidence: 99%
“…The distinct expression profile of CA‐MSCs corresponds with unique protumorigenic functions: (a) CA‐MSCs increase the CSC pool as marked by increased levels of ALDH and enhanced tumor sphere formation , and CA‐MSCs enhance (b) tumor growth and (c) chemotherapy resistance . Therefore, we determined if cancer stimulated OM MSCs classified as CA‐MSCs also developed CA‐MSC‐associated protumorigenic functions.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work demonstrates that axillary xenografts with ovarian cancer cell lines SKOV3 and CAOV3 do not form metastatic disease (13, 28). We next utilized primary patient derived ovarian tumor cells in an axillary xenograft model.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that co-injection of cancer cells with carcinoma associated mesenchymal stem cells (CA-MSC) can promote cancer growth via the formation of multiple components of the human tumor microenvironment though these xenografts do not spontaneously develop metastasis (13, 28). We sought to determine if a human microenvironment can increase ovarian cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…The microenvironment of cancer is complicated and can maintain stable survival advantages of PaC cells despite various perturbations [20, 21]. When the environment is not optimal, PaC cells can mediate adaptive changes such as stimulation of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%